Niche conservatism and geographical range expansion of Pomacea canaliculata and Pomacea maculata in non-native United States and China - Qin, Zhong; Zhang, Jiaen; Yao, Fucheng; Liu, Jimin; Shi, Zhaoji; Zhao, Benliang; Guo, Jing (Biological invasions, 2023)
The most noxious apple snails ( Pomacea canaliculata and P. maculata ) native to South America, currently have two distinct invaded ranges in China and the United States. Whether the environmental niches of the two closely related species have changed or remained stable (niche conservatism hypothesis) during the invasion process has become an important issue in forecasting their potential geographic distributions. For each Pomacea snail, two ecological niche models (ENMs, employing BIOMOD2) were generated based on bioclimatic variables and occurrence records in: (1) the native range; (2) the different invaded range. Conservation of ecological niche between the native and invasive snail populations was then tested by principal component and niche dynamics analysis. According to all models, precipitation contributed most to distribution of P. maculata , whereas low temperature was another most influential factor for spread of P. canaliculata . Niche conservatism was indicated by niche similarity tests and high niche stability for both Pomacea snails during their invasions in two regions. Niche expansions of P. canaliculata were relatively larger than unfilling values, whereas niche expansions of P. maculata were lower than unfillings. High niche unfilling for P. maculata in the United States revealed a great potential for further expansion in this region. We discussed the possible roles of physiological tolerances, genetic variation, residence time and hybridization in shaping niche changes for Pomacea snails during their invasion processes. Findings of this work can improve the understanding of potential mechanisms for niche differentiation and provide a theoretical basis for forecasting the invasion potential of Pomacea snails.